Head-to-head comparison of two human papillomavirus vaccines for efficacy against cervical intraepithelial neoplasia grade 3 and adenocarcinoma in situ—population-based follow-up of two cluster-randomized trials - Lehtinen, Matti; Gray, Penelope; Luostarinen, Tapio; Eriksson, Tiina; Apter, Dan; Bly, Anne; Harjula, Katja; Heikkilä, Kaisa; Hokkanen, Mari; Kuortti, Marjo; Nieminen, Pekka; Nummela, Mervi; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionWe report head-to-head comparison of the bivalent and quadrivalent HPV vaccine efficacies against immediate precursors of cervical cancer from 15 years’ country-wide cancer registry follow-up of phase III trial cohorts and an age-aligned cohort of unvaccinated women.MethodsThese individually and/or clusterrandomized cohorts of HPV6/11/16/18- and HPV16/18-vaccinated and unvaccinated women were enrolled, respectively, in 2002, 2004, and 2003/2005. The trial cohorts comprised initially 16- to 17-year-old HPV6/11/16/18-vaccinated FUTURE II (NCT00092534) participants (866) and HPV16/18-vaccinated PATRICIA (NCT00122681) and 012 trial (NCT00169494) participants (2,465), and 16,526 initially 16- to 19-year-old unvaccinated controls. After active 4-year clinical follow-up, passive, country-wide Finnish Cancer Registry (FCR) follow-up for cervical intraepithelial neoplasia grade 3 (CIN3) and adenocarcinoma in situ (AIS) was based on consented use of unique personal identifiers and started 6 months after the end of the FUTURE II and PATRICIA trials in 2007 and 2009, and ended at the end of 2019. The follow-up with altogether 229,020 follow-up years was age-aligned to ensure that similarly aged cohorts were passively followed up for 15 years post=vaccination for the intention-to-treat analyses of vaccine efficacy.ResultsOverall, we identified 5 and 16 CIN3 (no AIS) cases in the HPV6/11/16/18 and HPV16/18 cohorts, respectively, during the FCR-based follow-up. In the unvaccinated cohort, we identified 281 CIN3 cases, 20 AIS cases, and 13 cases with invasive cervical cancer. Vaccine efficacies against CIN3+ were 68.4% and 64.5% for the quadrivalent and the bivalent vaccines, respectively, with overlapping confidence intervals.DiscussionLong-term follow-up of randomized, initially adolescent HPV-vaccinated and unvaccinated cohorts shows, in this head-to-head setting, that the bivalent and quadrivalent HPV vaccines are equally effective against immediate precursors of cervical cancer.